Joint effects of atrial fibrillation and prothrombotic genotypes on the risk of venous thromboembolism - Erin Mathiesen Hald; Maja–Lisa Løchen; Kristian Hveem; Mary Cushman; Sigrid K. Brækkan; John–Bjarne Hansen (Research and Practice in Thrombosis and Haemostasis)
Background: Atrial fibrillation (AF) is a risk factor for venous thromboembolism (VTE), but the role of common prothrombotic gene variants in this relationship is unknown. Objectives: We investigated the joint effect of prothrombotic genotypes and AF on the risk of VTE in a population-based case-cohort. Methods: Incident VTE cases (n = 1458) and a subcohort (n = 14,526) randomly sampled from the Tromsø (1994-2012) and Trøndelag Health (1995-2008) cohort studies were included. DNA was genotyped for rs8176719 (ABO), rs6025 (factor V Leiden [FVL]), rs1799963 (prothrombin), rs2066865 (fibrinogen gamma gene), and rs2036914 (F11). Hazard ratios (HRs) with 95% CIs for VTE were estimated by individual single-nucleotide polymorphisms and categories of a genetic risk score (0-1, 2, 3, 4, and ≥5 risk alleles) in subjects with and without AF. Results: Over a median 12.3 years follow-up, 1421 participants were diagnosed with AF, of whom 139 developed subsequent VTE. Overall, participants with AF had a 1.7-fold increased risk of VTE (HR, 1.73; 95% CI, 1.43-2.08). Among those with AF, ≥1 risk allele of FVL was associated with 1.9-fold higher VTE risk (HR, 1.89; 95% CI, 1.13-3.17) compared with 0 risk alleles. None of the other single-nucleotide polymorphisms increased the risk. In participants without AF, the VTE risk increased linearly with increasing genetic risk score. No such association was found for those with AF. Conclusion: We confirmed that AF is a risk factor for VTE and showed that this relationship was augmented for carriers of FVL. Other common prothrombotic genotypes do not add additional risk of VTE to that induced by AF alone.